Effects of growing Coptis chinensis Franch in the natural understory vs. under a manmade scaffold on its growth, alkaloid contents, and rhizosphere soil microenvironment - Wang,Yu; Mo,Yu R.; Tan,Jun; Wu,Li X.; Pan,Yuan; Chen,Xia D. (PeerJ, 2022)
Background The main planting modes currently used for the production of Coptis chinensis Franch are under the shade of a manmade scaffold or a natural understory. In this study, we analysed changes in the growth, development, and alkaloids of C. chinensis when grown in a natural understory compared with under a manmade scaffold. We also clarified the differences in the rhizosphere soil microenvironment, represented by soil physicochemical factors, enzyme activity, and microbial community structure of 1- to 5-year-old C. chinensis between the different planting modes. These results will provide theoretical guidance and scientific evidence for the development, application, and extension of ecological planting technologies for C. chinensis. Results The results of this study showed that rhizome length, rhizome diameter, and rhizome weight all increased over time in both planting modes. The greatest rhizome length was reached in 4-year-old C. chinensis, while the greatest rhizome diameter and rhizome weight were obtained in 5-year-old C. chinensis. There was no significant difference in rhizome biomass between the two planting modes. The alkaloid content of the four common alkaloids in the rhizome of 5-year-old C. chinensis at the harvest stage met the standards found in the Pharmacopoeia of the People’s Republic of China; the berberine content and total alkaloids in the rhizomes were significantly higher with natural understory planting compared to planting under a manmade scaffold. A redundancy analysis revealed that the physicochemical factors and enzyme activity of rhizosphere soil were significantly correlated with variation in microbial community structure. Soil pH, available potassium, bulk density, available nitrogen, catalase, and peroxidase were all significantly correlated with bacterial and fungal community structures. Among these, soil pH was the most important factor influencing the structures of the fungal and bacterial community. In the two planting modes, the differences in soil enzyme activity and microbial community structure mainly manifested in the rhizosphere soil of C. chinensis between different growth years, as there was little difference between the rhizosphere soil of C. chinensis in a given growth year under different planting modes. The levels of nitrogen, phosphorus, potassium, and organic matter in the rhizosphere soil under either planting mode were closely associated with the type and amount of fertiliser applied to C. chinensis. Investigating the influence of different fertilisation practices on nutrient cycling in farmland and the relationship between fertilisation and the soil environment will be key to improving the yield and quality of C. chinensis medicinal materials while maintaining the health of the soil microenvironment.
Keywords: Coptis chinensis Franch; Growth and development; Soil physicochemical properties; Enzyme activities; Microbial communities